ALLIANCES AND RIVALRIES THE ARABIC QURAYSH TRIBES: INHIBITING FACTOR OF ISLAMIC DA’WAH IN MECCA 610-622 AD - Jati Pamungkas (LP2M IAIN Tulungagung, 2022)
The period of Islamic growth in Mecca from 610 to 622 AD can becategorized into a full challenges and full obstacles period. The Islamic da’wahdelivered by the Prophet Pbuh often encountered some constraints due to theresistance from the Quraysh leaders. At that time, it was difficult for Qurayshfigures to accept new beliefs, especially since Quraysh had a clan-based socio-cultural system consisting of 14 clans. Of the 14 clans or tribes in Quraish,there was competition for the political influence of Mecca which is recorded inhistory. The purpose of this study is to explain the obstacles to Islamic da’wahin Mecca caused by inter-clan politics among the Quraysh. The method usedin this study is a literature review method using primary sources from Arabic.This study explains that the hindrance to Islamic da’wah in Mecca before theProphet’s Pbuh migration to Medina were caused by socio-cultural factors ofthe people at that time, that is the competition between clans in Quraish.